Variability and Similarity of Gait as Evaluated by Joint Angles: Implications for Forensic Gait Analysis. Issue 2 (25th November 2013) - Yang, Sylvia X.M.; Larsen, Peter K.; Alkjær, Tine; Simonsen, Erik B.; Lynnerup, Niels
Abstract Closed‐circuit television (CCTV) footage is used in criminal investigations to compare perpetrators with suspects. Usually, incomplete gait cycles are collected, making evidential gait analysis challenging. This study aimed to analyze the discriminatory power of joint angles throughout a gait cycle. Six sets from 12 men were collected. For each man, a variability range VR (mean ± 1SD) of a specific joint angle at a specific time point (a gait cycle was 100 time points) was calculated. In turn, each individual was compared with the 11 others, and whenever 1 of these 11 had a value within this individual's VR, it counted as positive. By adding the positives throughout the gait cycle, we created simple bar graphs; tall bars indicated a small discriminatory power, short bars indicated a larger one. The highest discriminatory power was at time points 60–80 in the gait cycle. We show how our data can assess gait data from an actual case.